O trabalho no SAMU e a humanização do SUS: saberes-atividade-valores - Ana Rita Castro Trajano (2012)
Arising from debates on National Humanization Politics (PNH), regarded as transversal public policy of Unique Health System (SUS) support, we updated and reassert the universality, integralization, equalty/equalness and social participation principles. The wagingof triple inclusion method acquaints about the instituting power of PNH by engendering standard changes upon attention and management, whereof analysis devices and work process intervention, and while emphasizing the inclusion of subjects, collective and conflicts / analyzers. Attempting to analyze the work process and the PNH from the standpoint of industrious activity, within ergologic perspective (démarche), on which highlights the key triangle knowledge-activity-value. The Emergency Mobile Service (SAMU), in BeloHorizonte city, was elected as research field since humanization experiences through institutional support (from August, 2006 to December, 2008, when the present research was approved). By the time, it enquired how the standpoint of industrious activity mightinterfere/repercussion on the way of management in the work process of Samu, to the effect of SUS (Unique Health System) Humanization. Among the research instrumental strategies, features the activity acompaniment/observation, the work matters conversations and the semistructured interviews; including the Field Diary as reporting main tool. Moreover, we established the ergologic elaboration on act in competence ingredients as manner of activity entrance, as long as we selected five accompanied occurrences as analyses unities/ observedby the researcher or reported by the workers. Whereas In the activity analyses were identified ergologic clues, focused on the Dynamic Three-pole Device -DD3P- (one which is regarded as a research work management device, whereon is aimed a profitable dialoguebetween disciplinary knowledge pole and experience knowledge pole and only possible to produce by the experience in a third pole: the one of ethic and episthemological demands, born from the fecund meeting between the two other poles once linked with the guidelinesand PNH devices), and on the Collective Entities Relatively Pertinent (ECRP) - one which articulates to the activity (re)normalization debate - in order to further profound the National Humanization Politics upon Samu. Furthermore, possibilities of empowerment of collectiveactivity management spaces were identified, along with the share of knowledge and values, in compliance with the content provided by the ECRP, it could be treated on analysis and on intervention by the activity implied subjects. By these processes, was emphasize that theDD3P ergologic schema might help to find routes for the challenges concerning health work management process on SUS. The activity protagonists raised questions relating to the possibilities of work humanization on Samu, in regards of attention and managementundissociateness principles accomplish and of PNH transversality, on which features the acknowledgement and valorization (by the Regulation Central) of knowledge and values engendered in activity; the Reception with Risk Classification on Mobile Emergency, arisingfrom reflections on Health Emergency and Social Urgency, work conditions; underscoring salary matters, rest and nourishment time, psychological support, among other ones. Hence, by the end, it was highlighted that the research cycle does not encloses itself by the conclusion moment at all, and whence, its intend to create new opportunities of meetings and collective experimentations of producing knowledge upon work.